Morphological characterization and genetic diversity studies of promising brinjal genotypes for hybridization program in Bangladesh - Solaiman, Abul Hasnat Muhammad; Nishizawa, Takashi; Khatun, Mahmuda; Ahmad, Shahabuddin (JOURNAL OF ADVANCES IN AGRICULTURE, 2014)
In this Morphological variation of thirty-five brinjal genotypes was investigated in order to screen efficient genotypes for a hybridization program in Bangladesh. The phenotypic coefficient of variation (PCV) was higher than that for the genotypic. The PCV estimates were high for the number of branches, number of fruits per plant, and single fruit weight. Heritability estimates were high for the single fruit weight with high genetic advance. In spite of high heritability values for most traits, the expected genetic advance as a percentage of the mean ranged from 19.92 to 121.51. Multivariate analysis was performed using principal component analysis (PCA), principal coordinate analysis, cluster analysis and canonical variate analysis. With PCA, multivariate analysis of Mahalanobis's distance (D2), and cluster analysis, the genotypes were grouped into six clusters. The longest inter-cluster distance was between clusters II and III, and the shortest was between clusters V and VI. Cluster VI showed the longest intra-cluster distance but cluster II showed the shortest. Genotypes of cluster I were suitable for the number of branches per plant, cluster II for the fruit length, cluster III for the number of fruits per plant, and cluster IV for the single fruit weight and yield. Considering the performances, genotypes SM-111, SM-84, EGN-27, SM-183, and BARI begun-6 are suitable parents for the hybridization program.